1992
DOI: 10.1093/jnci/84.24.1887
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Fiber and Decreased Risk of Cancers of the Colon and Rectum: Evidence From the Combined Analysis of 13 Case-Control Studies

Abstract: If causality is assumed, we estimate that risk of colorectal cancer in the U.S. population could be reduced about 31% (50,000 cases annually) by an average increase in fiber intake from food sources of about 13 g/d, corresponding to an average increase of about 70%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(186 citation statements)
references
References 32 publications
1
174
0
11
Order By: Relevance
“…Fiber intakes (total, water-soluble, and waterinsoluble) have been reported to be inversely associated with the risk of colorectal cancer. 28 To examine whether the positive association for the Western dietary pattern was mediated by these nutrients, we included fiber intakes in the multivariate model. Further adjustment for fiber intakes did not alter this positive association for the Western dietary pattern score of females substantially: the RR for the comparison of the highest with the lowest quartile was 3.60 (95% CI ¼ 1.29-10.1) in distal colon.…”
Section: Resultsmentioning
confidence: 99%
“…Fiber intakes (total, water-soluble, and waterinsoluble) have been reported to be inversely associated with the risk of colorectal cancer. 28 To examine whether the positive association for the Western dietary pattern was mediated by these nutrients, we included fiber intakes in the multivariate model. Further adjustment for fiber intakes did not alter this positive association for the Western dietary pattern score of females substantially: the RR for the comparison of the highest with the lowest quartile was 3.60 (95% CI ¼ 1.29-10.1) in distal colon.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have suggested that a diet low in fat and high in fibre could be protective against colorectal cancer (Burkitt, 1971;Howe et al, 1992). Conversely, studies by Sandler et al (1993) have demonstrated that diets high in fat and low in fibre typical of those found in industrialised countries, increase the risk of the development of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds have been shown to be efficient for carcinogenesis prevention in animal models and humans as well. Several studies suggest that natural polyphenol compounds have a great effect on cancer protection (Howe et al., 1992). These compounds that are secondary metabolites in plants and polyphenol diet have shown promising against cancer (Lall, Syed, Adhami, Khan, & Mukhtar, 2015).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%